Effects of salinity, growth condition, and soil type on shoot dry matter of Alfalfa (Medicago sativa) – a meta-analysis. Issue 3 (4th February 2021) - Bansal, Sangeeta; Yin, Xinhua
ABSTRACT: Salinity is a spatially complex and dynamic property of soil that adversely impacts plant metabolism and rhizobium capacity for symbiotic nitrogen fixation, thus affecting alfalfa ( Medicago sativa ) growth. The objective of present study was to conduct the first meta-analysis to understand the influence of soil salinity, experimental growth condition, and soil type on alfalfa shoot dry matter. Thus, random-effects model meta-analysis was performed using Comprehensive Meta-Analysis (CMA) version 3 software across 10 published articles generating 68 observations. The effect sizes were determined as the natural logarithm of the response ratio as a metric response of alfalfa shoot dry matter under saline treatments versus the control treatment. Three moderators used in the study were: 1) Salinity, categorized as (low, 0–5 dS/m; medium, 6–15 dS/m; and high, 16–30 dS/m); 2) experimental conditions (field experiment, greenhouse, growth chamber); and 3) soil type (sand, sandy loam). Alfalfa shoot dry matter decreased significantly under medium and high salinity levels ( p ≤ 0.05); whereas low salinity did not have significant effect on shoot dry matter ( p ≥ 0.05). The decrease in shoot dry matter was 40, 43, and 50% under field, greenhouse, and growth chamber, respectively. In terms of soil type, sandy loam soil reduced the alfalfa shoot dry matter by 40%, whereas sandy soil showed a 59% decrease. Low saline soils (i.e., <5 dS/m) and/or sandy loam soil type under field conditions can increase alfalfa shoot dry matter and can outperform high saline soils (i.e., between 6 and 30 dS/m) and/or sandy soil under growth chamber conditions.